Sensory and cultural acceptability tradeoffs with nutritional content of biofortified orangefleshed sweetpotato varieties among households with children in Malawi - Hummel, Marijke; Talsma, Elise F.; Honing, A. van der; Gama, Arthur Chibwana; Vugt, Daniel van der; Brouwer, Inge D.; Spillane, Charles (Public Library of Science, 2018)
Background